2021
DOI: 10.1007/s40171-021-00285-7
|View full text |Cite
|
Sign up to set email alerts
|

Models for Predicting Non-Renewable Energy Competing with Renewable Source for Sustainable Energy Development: Case of Asia and Oceania Region

Abstract: Accurate energy forecasting is of great significance to meet the energy demands, clean energy plans and sustainable energy development strategies. Therefore, this study develops the integrated grey framework to forecast the growth trends of renewable and non-renewable energy production and consumption in Asia and Oceania region from 2017 to 2025 by using novel grey forecasting models, namely even grey model, discrete grey model, optimized discrete grey model and non-homogeneous discrete grey model (NDGM). Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…This study confirmed how flexibility moves toward the SDGs. Previous studies highlight the positive relationship between sustainability and resilience within decisionmaking processes in risk measurement (Settembre-Blundo et al, 2021); of the potential benefits associated with the implementation of a flexible consumption tax (Gerbeti, 2021); of the decisive contribution of renewable energy globally (Ikram, 2021); and in the resilience of the education sector following pandermia (Ahmed et al, 2021).…”
Section: Results Discussion and Implicationsmentioning
confidence: 99%
“…This study confirmed how flexibility moves toward the SDGs. Previous studies highlight the positive relationship between sustainability and resilience within decisionmaking processes in risk measurement (Settembre-Blundo et al, 2021); of the potential benefits associated with the implementation of a flexible consumption tax (Gerbeti, 2021); of the decisive contribution of renewable energy globally (Ikram, 2021); and in the resilience of the education sector following pandermia (Ahmed et al, 2021).…”
Section: Results Discussion and Implicationsmentioning
confidence: 99%
“…Geothermal energy can support base-load electricity supply and external factors such as weather and climate do not influence the energy source and the energy source is available throughout the year (MIT 2006 ; DiPippo 2012 ). Thus, costwise and efficiencywise geothermal, in general, is economically the most cost-effective energy source (Ikrim 2021 ) especially in Turkey (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…This cost does not exist in the case of electricity generated from the geothermal energy source. Thus, electricity generated from geothermal energy sources is much cheaper compared to the electricity generated from fossil fuels energy sources (Ikram 2021 , Baba and Chandrasekaram, 2022 ). In addition to the future cost reduction due to advancement in drilling technology, the advantage that Turkey (western Anatolian region) has is the presence of Curie depth point at shallower depth (~ 12 km) and high heat flow values over the entire region (Akin et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gerbeti ( 2021 ) discussed several flexible proposals for controlling industrial emissions in the way of achieving environmental sustainability. Ikram ( 2021 ) developed a sustainable energy development grey model for predicting renewable and non-renewable energy production and consumption. Settembre-Blundo et al ( 2021 ) developed a risk management tool focusing on business sustainability, which can measure the progress of achieving SDGs.…”
Section: Introductionmentioning
confidence: 99%